Multigene phylogeny reveals a cryptic diversity in the genus Dinobryon (Chrysophyceae) with integrative description of five new species - Jeong, Minseok; Wang, Yitong; Kim, Jong Im; Shin, Woongghi (Frontiers in Plant Science, 2023)
The genus Dinobryon is one of the most recognizable chrysophyte genera, characterized by dendroid colonies with a biflagellate inside each cellulosic lorica. The representative forms of lorica are cylindrical, conical, vase, or funnel shaped, with undulation on the lorica wall. Traditionally, the morphological characteristics of the lorica and the colony organization have been used for the delimitation of Dinobryon species. To understand the taxonomy and phylogeny of colonial Dinobryon species, we performed molecular and morphological studies using 39 unialgal cultures and 46 single colony isolations from environmental specimens collected in Korea. We used a nuclear internal transcript spacer (ITS1-5.8S-ITS2) to find the genetic diversity of Dinobryon from environmental samples and a combined dataset from six gene sequences (nuclear SSU and LSU rRNA, plastid LSU rRNA, rbcL and psaA, and mitochondrial CO1 genes) for phylogenetic analysis. We found 15 different lineages based on the genetic diversity of the nuclear ITS sequences. The phylogenetic tree of the colonial species based on the combined multigene dataset were divided into 18 subclades, including five new species, each with unique molecular signatures for the E23-5 helix of the V4 region in the nuclear SSU rRNA and the E11-1 helix of D7b, and the E20-1 helix of D8 regions in the nuclear LSU rRNA. Morphological studies were focused on lorica dimension and shape, and stomatocyst morphology. The Dinobryon species showed similarities or differences in lorica morphologies between and within species, and also differences in lorica size between culture and environmental samples. Five Dinobryon species formed distinctive stomatocysts, their stomatocyst morphologies, including collar structure, surface ornamentation, and cyst shape, showed unique characteristics in each species and were useful for identification. Here, we propose five new species based on morphological and molecular evidences: D. cylindricollarium, D. exstoundulatum, D. inclinatum, D. similis, and D. spinum.